HARMONIZATION OF SOCIO-CULTURAL LIFE IN MULTI-ETHNIC COMMUNITIES IN VILLAGES - Kalip; Arief Fahmi Lubis; Naro Pandapotan Pasaribu (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research discusses the strategies and efforts made to harmonize socio-cultural life in multi-ethnic communities in villages. In the context of ethnic diversity, socio-cultural harmony is a crucial aspect for creating a stable, peaceful and productive society. This research uses a qualitative approach with field study methods and in-depth interviews to collect data from various ethnic groups in the village. The results of this research show that the success of socio-cultural harmonization is greatly influenced by: Inclusive Infrastructure Development which provides public facilities and public spaces that are accessible to all citizens. Promotion of Culture and Tradition through cultural festivals, multicultural education, and programs that appreciate the contributions of all ethnicities. Increased Political Participation by including representatives from each ethnic group in village decision making. Women's Empowerment which focuses on increasing the role and contribution of women in the community. Monitoring and Evaluation with the development of clear metrics to assess harmonization progress and identify areas requiring improvement. This research concludes that socio-cultural harmonization in multi-ethnic villages can be achieved through a holistic and collaborative approach. Integrative efforts, involving all levels of society, are needed to create a just, tolerant and harmonious environment. Pragmatically, socio-cultural harmonization not only maintains social cohesion but also promotes sustainable development and the welfare of all village residents.